Risk Analysis of Musculoskeletal Disorders (MSDs) Complaints on Batik Crafters Under The Assistance of Ademos Indonesia - Shintia Yunita Arini; Dani Nasirul Haqi (Institute of Medico-legal Publications Pvt Ltd, 2021)
Introduction: Batik is one of Indonesia’s original works of art that is continuously preserved in severalregions in Indonesia. Several people working as batik crafters in Bojonegoro, East Java, Indonesia areunder the assistance of Ademo. Based on the preliminary study conducted, most batik crafters had startedto complain of pain in several parts of their body, which was considered due to work postures and nonergonomic work stations. Thus, this study was conducted to analyze the risk of Musculoskeletal Disordersusing RULA and NBM.Materials and Methods: It was an observational study with cross sectional design. Data collection wasconducted by conducted observation using RULA (Rapid Upper Limb Assessment), NBM (Nordic BodyMap) and interviews with batik crafters in home industry. The population in this study was 42 batik craftersin a batik industry under the assistance of Ademos Bojonegoro. This study utilized total sampling techniqueby which the whole population were taken as the sample.Results: The results showed that 76.2% of batik crafters had a very high risk of MSDs on the right side ofthe body and on the left side of the body; 50% of batik crafters had a high risk of MSDs; and 50% had a veryhigh risk of MSDs. The results of observations using NBM showed that 42.85% had a high risk of MSDs.Conclusion: This study concludes that all the batik crafters are in an emergency circumstance experiencingmusculoskeletal disorders and need an ergonomic work station as soon as possible.